2022
DOI: 10.13005/bpj/2439
|View full text |Cite
|
Sign up to set email alerts
|

Runt-Related Transcription Factor 2 (Runx2) Measurement in Phytoestrogen-Induced Bone: A Comparison of Western Blot and Immunohistochemistry Methods

Abstract: Estrogen deficiency can contribute to osteoporosis in postmenopausal women. Phytoestrogens are becoming more widely recognized as potential estrogen replacement therapy. The administration of phytoestrogens can cause bone formation, which is marked by an increase in Runx2 expression in osteoblast cells and can be seen using western blot and immunohistochemistry approaches. This review aimed to compare the detection methods of Runx2 in phytoestrogen-induced bone tissue using western blots and immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Traditionally, the quantification of ALP and RUNX2 has relied on laborious and often expensive techniques, including enzyme-linked immunosorbent assays (ELISAs) [20,21], Western blotting [22,23], and polymerase chain reaction (PCR) [24,25]. These methods, while valuable for research, are impractical for rapid, point-of-care diagnostics or realtime monitoring of osteogenic processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the quantification of ALP and RUNX2 has relied on laborious and often expensive techniques, including enzyme-linked immunosorbent assays (ELISAs) [20,21], Western blotting [22,23], and polymerase chain reaction (PCR) [24,25]. These methods, while valuable for research, are impractical for rapid, point-of-care diagnostics or realtime monitoring of osteogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mahato et al [34] developed an impedimetric biosensor using gold-nano-dendroids and graphene oxide (GO) detecting ALP in human serum samples, Liu et al [35] describe a fluorescent assay based on GO and λ exonuclease for ALP activity, while to the best of our knowledge, RUNX2 detection is still performed using classical techniques like quantitative PCR (qPCR) [36], Western blot [37], and immunohistochemistry [38], while no progress has been made regarding the development of a novel electrochemical biosensor to detect this biomarker. Ma'arif et al [22] compared two techniques used for RUNX2 detection in bone tissue, i.e., Western blot and immunohistochemistry, investigating 70 articles, and concluded that the Western blot method is superior in terms of sensitivity, selectivity, cost, and detection time. However, neither of these techniques gives a fast response, the Western blot method having a process time over 25 h, while immunohistochemistry takes over 46 h to generate a result.…”
Section: Introductionmentioning
confidence: 99%